5(c-4)=3c+6

Simple and best practice solution for 5(c-4)=3c+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(c-4)=3c+6 equation:


Simplifying
5(c + -4) = 3c + 6

Reorder the terms:
5(-4 + c) = 3c + 6
(-4 * 5 + c * 5) = 3c + 6
(-20 + 5c) = 3c + 6

Reorder the terms:
-20 + 5c = 6 + 3c

Solving
-20 + 5c = 6 + 3c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-3c' to each side of the equation.
-20 + 5c + -3c = 6 + 3c + -3c

Combine like terms: 5c + -3c = 2c
-20 + 2c = 6 + 3c + -3c

Combine like terms: 3c + -3c = 0
-20 + 2c = 6 + 0
-20 + 2c = 6

Add '20' to each side of the equation.
-20 + 20 + 2c = 6 + 20

Combine like terms: -20 + 20 = 0
0 + 2c = 6 + 20
2c = 6 + 20

Combine like terms: 6 + 20 = 26
2c = 26

Divide each side by '2'.
c = 13

Simplifying
c = 13

See similar equations:

| 4w+7-2w+5-2w= | | 0.15-0.2x=0.3(x*3) | | 10p+9-11-p=-2(2p+4)+3(2p+2) | | r-17.1=-48 | | 6x+18y=48 | | (x-8)(x-2)=-9 | | 3k(k+7)=(k-2)(k-2) | | 2x-9x+11=32 | | -4(-4p-5)=2[-2p-3(-p+1)] | | 5x-23+x+29+90=180 | | 2x^2-25x-4=0 | | 15=-12+9x | | 180-108=x | | y=-2x-8x+5 | | x-180=0 | | .77x=28 | | -3x-6y-12=0 | | 18-1x=-7x+30 | | 2x+y=14-3x | | -3n(n^2+2n)= | | 4w+5w+1w= | | x(x+1)(x+2)(x+3)=360 | | 0.333y-0.5=0.1666y | | 4(2x-3)+1=9 | | 3.25=4.3r+16-r | | 2y-6=2x-6 | | ln(x)=.71 | | 6(x-6)+14=6x-21 | | 2(x+4)+2(x-2)=3x+12 | | 6y-8x=12 | | -8m-5m=13 | | 18x-4x=7 |

Equations solver categories